CSR (Corporate Social Responsibility) in India: Challenges and Issues: Understanding the challenges and prospects of CSR implementation in India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Business social responsibility (CSR) has become an important topic of public policy in India'scorporate landscape, thanks in part to the growing social regulatory forces that have enabled CSR toestablish long-term relationships with society. An organisation or person has a duty to behave in waysthat benefit society as a whole, according to the concept of social responsibility. For the economy andecology to remain in balance, each person and organisation has a responsibility to perform. In 1953,William. Bowen published the book 'Social Responsibilities of Business', which was the first reference tothe phrase corporate social responsibility. When it comes to philanthropy, service to the community, andcorporate responsibility (CSR), India has a long history of intimate company participation in thesocioeconomic concerns that are critical to the country's long-term growth. Human resources areassumed to be the foundation of all economic endeavours. The primary goal of this study is to find outhow future Indian business executives feel about Corporate Social Responsibility (CSR). Indiancorporations like Tata and Nestle have been implementing CSR for decades, even before the term wascoined. Even though there are several instances of successful CSR initiatives in India, the movement isstill in its infancy. Many huge corporations are marketing their CSR initiatives in the media while doingso in a shallow manner. For the purposes of this study, the obstacles and difficulties experienced byIndian CSR activities were discovered and reviewed.